Anti-bacterial activity of Rosela Flower Extract (Hibiscus sabdariffa L.) against Extended-Spectrum Beta-Lactamase (ESBL) Eschericia coli - Muhammad Mu’amar Fathoni; Isnaeni Isnaeni; Asri Darmawati (Berkala Ilmiah Kimia Farmasi, 2021)
Roselle (Hibiscus sabdariffa L.) contains cyanidin-3-rutinoside, delphinidin, delphinidin-3-monoglucoside, cyanidin-3-monoglucoside, cyanidin-3-sambubioside, cyanidin-3,5-diglucoside may inhibit the growth of Extended-Spectrum-Beta-Lactamase (ESBL) Escherichia coli, but there is no research reported the determination of MIC of Roselle (Hibiscus sabdariffa L.) extract powder against ESBL E.coli ATCC 6110 and ATCC 5949 and their potency ratio compared to meropenem. This study aimed to determine the MIC of Roselle flower extract powder on the growth of ESBL E. coli ATCC 6110 and ATCC 5949 and determine the potency ratio compared to meropenem. This study used two methods in determining MIC, namely the agar diffusion method and the dilution method with Nutrient Agar media which was incubated at 37 ±1°C for 24 hours, while the determination of the potency ratio was carried out by diffusion method with the same media which was incubated at 37 ±1°C for 24 hours. The results obtained were diameter of inhibition zone (mm) which were then observed and analyzed to calculate the potency ratio. The results showed that the MIC of Roselle flower extract powder was obtained at a concentration of 12,500 ppm by diffusion method and at a concentration of 3,125 ppm by dilution method with 24 hours incubation at 37 ± 1o C and the potency ratio of Roselle flower extract powder compared to meropenem was 89.7% and 97.97% against ESBL E.coli ATCC 6110 and ESBL E.coli ATCC 5949 respectively.